2003
DOI: 10.1016/s0210-4806(03)72974-x
|View full text |Cite
|
Sign up to set email alerts
|

Metástasis retrorbitaria como manifestación inicial del cáncer de próstata

Abstract: Orbital metastasis is an unusual localization within tumoral dissemination of prostatic cancer. Similarly, it is rare that orbital metastasis might be responsible for the clinic manifestations that determine the initial diagnosis of neoplasia. We illustrate the case of a patient suffering from prostatic adernocarcinoma that displayed alterations of facial sensitivity and right eye exophthalmos. We describe how the final diagnosis was reached and the patient's response to the suppressive hormonal treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A review of periorbital prostatic metastases reported a survival of 16.3 months, showing no statistically significant differences when compared to other prostatic metastases [6]. However, there are cases with longer survival rates [7], as it is our case.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…A review of periorbital prostatic metastases reported a survival of 16.3 months, showing no statistically significant differences when compared to other prostatic metastases [6]. However, there are cases with longer survival rates [7], as it is our case.…”
Section: Discussionmentioning
confidence: 64%
“…The most common metastatic sites of the prostatic adenocarcinoma are the pelvic lymphatic nodes and the bones of the axial skeleton. Intracranial metastases are unusual, and when they occur, the diagnosis of prostate cancer is already made and the disease is already disseminated [6]. It is exceptional that a cranial metastasis appears as a first manifestation of a prostate cancer, as it is our case.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations